CURRENT APPROACHES TO MORPHOLOGIC DIAGNOSIS OF TUBERCULOSIS - V. A. Tsinzerling; M. M. Agapov (Туберкулез и болезни лёгких)
The article describes the most pertinent techniques for morphologic diagnosis of tuberculosis incorporating the related problems encountered by practicing pathologists including frequently meet co-infection with HIV, increase of non-tuberculous mycobacterioses and detection of mycobacteria possessing atypical properties presented by coccus and branching forms. The detection of causative agents located extracellular is discussed as well as their potential ability to form biofilms.